PD-L1 expression as poor prognostic factor in patients with non-squamous non-small cell lung cancer - Zhou, Cuiling (Oncotarget, 2017)
OBJECTIVES: The role of programmed cell death ligand 1 (PD-L1) in non-small cell lung cancer (NSCLC), especially according to histologic type, remains controversial. The purpose of this study was to assess PD-L1 expression and its association with overall survival (OS) and clinicopathologic characteristics in NSCLC. MATERIALS AND METHODS: Formalin-fixed paraffin-embedded specimens were obtained from 108 patients with surgically resected primary NSCLC. PD-L1 expression was assessed via immunohistochemistry using a histochemistry score system. The relationship between OS or clinicopathologic characteristics and PD-L1 expression was evaluated via the Kaplan-Meier method and Cox proportional hazards model, respectively. RESULTS: Of 108 NSCLC specimens, 44 had high PD-L1 expression, which was highly associated with histologic type (p = 0.003). Patients without PD-L1 expression had remarkably longer OS than those with PD-L1 expression (median OS: 96 months vs. 33 months, p < 0.001). In the subgroup analysis of non-squamous cell carcinoma, OS was more favorable in those without PD-L1 expression than in those with PD-L1 expression (median OS: 113 months vs. 37 months, p < 0.001). Multivariate analysis revealed that PD-L1 expression (95% confidence interval 1.459-4.520, p < 0.001), male sex and higher tumor-node-metastasis stage were significantly correlated with shorter OS. CONCLUSIONS: This study demonstrated that PD-L1 expression is an independent prognostic factor for poor survival in NSCLC patients, especially those with non-squamous NSCLC.